1999
DOI: 10.1161/01.str.30.6.1190
|View full text |Cite
|
Sign up to set email alerts
|

Early Neurobehavioral Outcome After Stroke Is Related to Release of Neurobiochemical Markers of Brain Damage

Abstract: Background and Purpose--The study aimed to investigate the predictive value of neurobiochemical markers of brain damage (protein S-100B and neuron-specific enolase [NSE]) with respect to early neurobehavioral outcome after stroke. Methods--We investigated 58 patients with completed stroke who were admitted to the stroke unit of the Department of Neurology at Magdeburg University. Serial venous blood samples were taken after admission and during the first 4 days, and protein S-100B and NSE were analyzed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
181
1
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(205 citation statements)
references
References 33 publications
9
181
1
12
Order By: Relevance
“…One piece of evidence which can support this hypothesis is the relationship between the degree of neuronal damage and the serum NSE level following a cerebral stroke (Cunningham et al, 1991(Cunningham et al, , 1996DeGiorgio et al, 1995DeGiorgio et al, , 1999Fogel et al, 1997;Missler et al, 1997;Martens et al, 1998;Buttner et al, 1999;Schoerkhuber et al, 1999;Wunderlich et al, 1999) or other neuronal brain damage (DeGiorgio et al, 1995(DeGiorgio et al, , 1999Fogel et al, 1997;Martens et al, 1998; Buttner et al, 1999;Schoerkhuber et al, 1999). In these diseases, the serum NSE level exhibits a prognostic indication inasmuch as studies have found a close relationship between the volume of affected neuronal tissue and the serum NSE level (Cunningham et al, 1991(Cunningham et al, , 1996Missler et al, 1997;Wunderlich et al, 1999). We hypothesize that the poor outcome of patients with a high NSE level and brain metastasis is due to the severity of normal neuronal tissue damage surrounding metastases.…”
Section: Discussionmentioning
confidence: 99%
“…One piece of evidence which can support this hypothesis is the relationship between the degree of neuronal damage and the serum NSE level following a cerebral stroke (Cunningham et al, 1991(Cunningham et al, , 1996DeGiorgio et al, 1995DeGiorgio et al, , 1999Fogel et al, 1997;Missler et al, 1997;Martens et al, 1998;Buttner et al, 1999;Schoerkhuber et al, 1999;Wunderlich et al, 1999) or other neuronal brain damage (DeGiorgio et al, 1995(DeGiorgio et al, , 1999Fogel et al, 1997;Martens et al, 1998; Buttner et al, 1999;Schoerkhuber et al, 1999). In these diseases, the serum NSE level exhibits a prognostic indication inasmuch as studies have found a close relationship between the volume of affected neuronal tissue and the serum NSE level (Cunningham et al, 1991(Cunningham et al, , 1996Missler et al, 1997;Wunderlich et al, 1999). We hypothesize that the poor outcome of patients with a high NSE level and brain metastasis is due to the severity of normal neuronal tissue damage surrounding metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Only median CRP levels in group H significantly decreased from 25 (22-33) to 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) mg/dL 3 days after study entry (PM10) and to 7 (2-13) mg/dL at the end of the observation period, but did not reach the normal range (Figure 2). Although CRP values in group H were slightly higher from PM1 (study entry) to PM8 (42 h after study entry), median 2 Serum S-100B, IL-8, and plasma PMN elastase levels, as well as serum CRP levels and fluid balance within the first 6 days of septic shock.…”
Section: S-100b/il-8 Serum and Pmn Elastase Plasma Levels After Randomentioning
confidence: 98%
“…Measurement of the neuroprotein S-100B released into the circulation was considered as a reliable procedure in detecting brain damage due to isolated traumatic brain injury (17), stroke (18), hemorrhage (19) or global ischemia (20,21). Increased S-100B serum levels have also been observed to correlate with the duration of cardiopulmonary bypass surgery (22) and the associated development of neurological complications (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of circulating CNS antigens after stroke reflects the severity of cell injury and predicts the outcome (Herrmann et al, 2000;Wunderlich et al, 1999). If these antigens were presented to lymphocytes in the proper context, an autoimmune response to brain could develop.…”
Section: Introductionmentioning
confidence: 99%